The Degree of Authority Delegation and its relation to the Degree of Administrative Creativity at the Government Secondary School Principals From the Point of View of the Teachers in the Kasbah Brigade of Oman - Kaddah, Mohammad; Shalabi, Eman Mufdi (Dirasat: Educational Sciences, 2021)
This study aims to realize the relationship between the authority delegation and the administrative creativity of high secondary school managers according to the opinion of teachers in the Capital of Amman (Al-Qasba). The researchers followed the descriptive approach through the development of two questionnaires distributed to teachers of public secondary schools in the brigade of the Kasbah Amman. The study sample consists of 250 teachers (male and females), and the methodology of selection is random selection. Two main tools are used for data collection: the first one is measuring the degree of authority delegation; the second is measuring the degree of administrative creativity of high secondary school managers. The tools were distributed and submitted to the study sample, after ensuring that the tools are valid and applicable. The results show a medium level for each degree of authority delegation level and administrative creativity level. In addition, the results show a statistically positive relationship between the degree of authority delegation and the administrative creativity of the sample study. Results do not show statistical variables related to educational qualification variables at the significant level for the degree of administrative creativity of high secondary school managers. At the same time, results show statistical variables related to gender and experience variables at a significant level for the degree of administrative creativity of high secondary school managers. Referring to the results of the study. The researcher recommends conducting periodical meetings with the employees to keep them updated with the latest development techniques related to administrative fields, and conducting training sessions about delegation of authority. Finally, the Ministry of Education shall assign the schools manager based on international standards.